Tubal re-anastomoses through a mini-laparotomy incision - Ashok R. Anand; Jain, Aditi R.; C. Pushpa; Adithi Jayaprakash (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
To assess the feasibility and reproducibility of tubal anastomosis through a mini-laparotomy incision. Study design is descriptive case study at Academic Medical Center. Sixteen patients with previous tubal sterilization requesting for tubal re-anastomosis. Systematization of the operative steps for tubal re-anastomosis using a mini-laparotomy incision. Primary outcome measures were feasibility and reproducibility; secondary measures were tubal patency, operative time, complications, and ergonomic qualities. The 31 tubes were successfully re-anastomosed and patency was confirmed. The mean surgical time was 15 minutes per tube. Tubal re-anastomosis after tubal sterilization can be performed through a mini-laparotomy incision. Systematization of the operative steps allowed the performance of the operation at speed. More extensive series and follow-ups are needed to assess post-operative pregnancy rates.